2022
DOI: 10.1002/joc.7875
|View full text |Cite
|
Sign up to set email alerts
|

Innovative polygon trend analysis of monthly precipitation (1952–2015) in the Hindukush‐Karakoram‐Himalaya river basins of Pakistan

Abstract: The Hindukush-Karakoram-Himalayas (HKH) mountainous range supplies water to 10 river basins serving eight countries. The present study focuses on the river basins located within the HKH region in Pakistan. The modified Soil and Water Assessment Tool (SWAT+) was used to split the research region into 13 subbasins. The Mann-Kendall, Sen's slope, innovative polygon trend analysis (IPTA), and innovative trend analysis (ITA) methods were used for the monthly precipitation time series. The Shyok sub-basin (central K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 98 publications
1
1
0
Order By: Relevance
“…Similar to Hussain, et al [27], we observed significantly increasing runoff trends in CRB on a seasonal and annual scale, except in autumn. Overall, precipitation increased in the region, except in annual and spring during 1964-2012 in the CRB, as these findings agree with those of [73]. Annual precipitation and mean annual runoff displayed increasing trends, and [26] attributed the increase in precipitation and snow cover to the possible reasons for increased runoff in the CRB.…”
Section: Discussionsupporting
confidence: 76%
“…Similar to Hussain, et al [27], we observed significantly increasing runoff trends in CRB on a seasonal and annual scale, except in autumn. Overall, precipitation increased in the region, except in annual and spring during 1964-2012 in the CRB, as these findings agree with those of [73]. Annual precipitation and mean annual runoff displayed increasing trends, and [26] attributed the increase in precipitation and snow cover to the possible reasons for increased runoff in the CRB.…”
Section: Discussionsupporting
confidence: 76%
“…This method has been developed recently (Şen et al, 2019). Compared to ITA, IPTA detects trends in time series, visualizing the increasing/decreasing trend and the transition between months/seasons as polygons (Ahmed et al, 2022). IPTA offers several advantages over other conventional methods, including:…”
Section: Ipta Methodsmentioning
confidence: 99%